1995
DOI: 10.1136/gut.36.6.825
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying of a solid meal is accelerated by the removal of dietary fibre naturally present in food.

Abstract: Exogenous fibre added to liquid meals delays gastric emptying. Its effect on solid meals is uncertain, and nothing is known of the effect on gastric emptying of fibre naturally present in food. This study therefore looked at gastric emptying of two different solid meals in eight healthy subjects and their blood glucose responses. The meals were exactly equivalent except for the total dietary fibre content (high fibre 20 g, low fibre 4 g of dietary fibre per 1000 kcal) and supplied 870 kcal (700 kcal women), 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 40 publications
1
85
0
Order By: Relevance
“…A range of studies have demonstrated that inclusion of viscous fibers in liquid test meals results in delayed gastric emptying, and are particularly consistent in the case of pectins in human studies [126,127]. In a study comparing the physiological effects of a mixed meal containing high levels of natural fibers (fruit, vegetables and whole grains) against one without these fibers (instead containing fruit and vegetable juice and refined grains), concluded that removal of natural fiber decreased gastric emptying mean rate of approximately 45 min in a crossover feeding trial in 8 healthy adult participants [128]. The dietary fibers that raise the bulk of luminal contents of the large bowel are those that are not well fermented by the colonic microflora, and those that have a high water-binding capacity [84].…”
Section: Digestive and Absorptive Functions Of The Gastrointestinal Tmentioning
confidence: 67%
“…A range of studies have demonstrated that inclusion of viscous fibers in liquid test meals results in delayed gastric emptying, and are particularly consistent in the case of pectins in human studies [126,127]. In a study comparing the physiological effects of a mixed meal containing high levels of natural fibers (fruit, vegetables and whole grains) against one without these fibers (instead containing fruit and vegetable juice and refined grains), concluded that removal of natural fiber decreased gastric emptying mean rate of approximately 45 min in a crossover feeding trial in 8 healthy adult participants [128]. The dietary fibers that raise the bulk of luminal contents of the large bowel are those that are not well fermented by the colonic microflora, and those that have a high water-binding capacity [84].…”
Section: Digestive and Absorptive Functions Of The Gastrointestinal Tmentioning
confidence: 67%
“…Experimental manipulations of glycemia in human subjects confirmed this hypothesis (Gielkens et al 1998). In contrast to the notion that hyperglycemia induces satiety, enhanced satiety sensations (van Amelsvoort and Weststrate 1992), delayed onset of hunger (Benini et al 1995), and/or decreased ad libitum energy intake (Ludwig et al 1999) have been reported following the intake of low-GI foods or meals that induce modest post-intake rises in glycemia (Brand-Miller et al 2002). This field remains controversial, and conflicting reports suggest that the GI is not a reliable predictor of satiety effects (Geliebter et al 2013).…”
Section: Macronutrients and Satiety: From Classical Theories Of Appetmentioning
confidence: 80%
“…There is a relatively high inter-individual variation in the rate of gastric emptying, whereas the intra-individual variation is low when subjects are eating the same diet [31]. Several studies indicate that the addition of viscous soluble fibers to the meal [32], as well as fibers naturally present in food [33], reduces the gastric emptying rate and the glycemic response to a test meal. Delayed gastric emptying leads to a sustained gastric distention and a prolonged exposure of nutrients and energy to the intestinal lumen [7].…”
Section: Discussionmentioning
confidence: 99%